Search for a heavy composite Majorana neutrino in events with dilepton signatures from proton-proton collisions at s=13 TeV - KAYA, MİTHAT (My University, 2023)
Results are presented of a search for a heavy Majorana neutrino [Formula presented] decaying into two same-flavor leptons ℓ (electrons or muons) and a quark-pair jet. A model is considered in which the [Formula presented] is an excited neutrino in a compositeness scenario. The analysis is performed using a sample of proton-proton collisions at s=13TeV recorded by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of 138fb−1. The data are found to be in agreement with the standard model prediction. For the process in which the [Formula presented] is produced in association with a lepton, followed by the decay of the [Formula presented] to a same-flavor lepton and a quark pair, an upper limit at 95% confidence level on the product of the cross section and branching fraction is obtained as a function of the [Formula presented] mass [Formula presented] and the compositeness scale Λ. For this model the data exclude the existence of [Formula presented] ([Formula presented]) for [Formula presented] below 6.0 (6.1) TeV, at the limit where [Formula presented] is equal to Λ. For [Formula presented], values of Λ less than 20 (23) TeV are excluded. These results represent a considerable improvement in sensitivity, covering a larger parameter space than previous searches in [Formula presented] collisions at 13 TeV.
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; CMS; Composite fermions; Heavy leptons; LHC